Developing Leaders for International Baccalaureate World Schools. (August 2018) - Calnin, Gerard; Waterson, Mark; Richards, Sue; Fisher, Darlene
A significant corpus of research now consistently confirms that school leadership is the second most important in-school variable to impact on student outcomes. Investing in leaders and aspiring leaders is therefore an imperative for schools and school systems. However, much of the educational leadership research emerges from national systems of education, with a largely Western set of norms and assumptions. To what extent, it can be asked, are the attributes and capabilities described in the literature applicable on a more universal or global scale? A paucity of research addresses this question and explores educational leadership in trans-national and multi-cultural settings. The International Baccalaureate (IB), with its 4500 schools in more than 135 countries, has responded to the challenge of developing leaders for its schools (known as IB World Schools). Regardless of the strength of research within particular national or cultural contexts, the IB's complex and globally dispersed school network means that leaders cannot be expected to follow a single model or paradigm of leadership practice. The IB acknowledges that effective leadership takes into account the environment within which leaders work. At the heart of an IB school leader's challenge is to develop strong capabilities in cultural and contextual awareness, as well as a deep understanding of the types of leadership practices that have the best chance of maximising student and organisational outcomes in different contexts. The IB has developed a distinctive leadership programme to support IB leaders and build their capabilities in these vital areas. This paper outlines the contexts, research and theorising that has led to the IB leadership professional development programme. It also presents the aims, guiding principles and key features, inclusive of the key capabilities and intelligences that are the core components of the learning and development experience. The question raised at the conclusion of this paper is: to what extent are these capabilities applicable for leaders not only in IB World Schools but in schools more widely?